Analysis of The Relationship Between Work Posture and Complaints of Musculoskeletal Disorders (MSDS) In Workers Of Sri Tanjung Cracker Factory, Indramayu, In 2024 - Latif, Idham; Fauzi, Muhamad; Fitriyani, Saskiya (Jurnal Medisci, 2025)
Background. Musculoskeletal complaints refer to issues within the skeletal muscles experienced by an individual, varying from slight discomfort to severe agony. An improper working posture significantly increases the likelihood of musculoskeletal diseases, particularly in the lumbar and cervical regions. At the Sri Tanjung cracker facility in Kenanga Indramayu Village, there were reports of Musculoskeletal Disorders (MSDs) with differing incidence rates, including symptoms of pain in the back, neck, waist, shoulders, arms, and wrists. A continually adopted ergonomically unsound work posture, along with large workloads and extended durations, can jeopardize worker safety. Aims. This study aimed to investigate the correlation between work posture and the prevalence of Musculoskeletal Disorders (MSDs) among employees at a cracker factory. Methods. The employed methodology was an analytical study utilizing a cross-sectional design. The research population encompasses all employees in the production department of the Sri Tanjung cracker factory, totaling around 50 individuals, which constitutes the entire population—data analysis with Pearson's chi-squared statistical tests. Result. The study identified work position as the statistically significant variable influencing the incidence of Musculoskeletal Disorders (MSDs) (p = 0.031). Conclusion. Work posture is a contributing factor to Musculoskeletal Disorders (MSDs) among workers at the Sri Tanjung cracker industry. Implementation. Consequently, manufacturing workers can enhance their awareness of Musculoskeletal Disorders (MSDs) via social media platforms, improve their work posture, and engage in stretching exercises for limbs subjected to awkward positions.